Projection of Water Utilities for Customers in East Timor-Leste in Dili for Sustanaible Development Goals (SDGs) 2030 - Geazi Isai Reis dos Santos; F Roslan Edy Santosa (NAROTAMA UNIVERSITY, Indonesia)
Water in human life has a very vital function. The daily activities of humans never escape from water. Starting from bathing, washing, cooking up to the elements of human body One is also composed of water. To obtain the projected results of population growth for the next 10 years, the calculation of water discharge in Dili City. Population projections with geometric methods use the assumption that the number of people will increase geometric. The rate of growth is considered the same for each year. Of the increase of population in the year 2017 population growth in Dili by 12.8% with a population of 234,062, used as a reference for the projected population for the next 10 years (2017-2027). Based on the increase of population used is 12.8% and the population is 10 years (2018-2027) for 2.395.75 inhabitants. The balance of clean water needs in urban clean water services.